2018
DOI: 10.1111/ecin.12719
|View full text |Cite
|
Sign up to set email alerts
|

The Turkish Current Account Deficit

Abstract: During the 2011–2015 period, Turkey's current account deficit as a percentage of gross domestic product (GDP) was one of the largest among the Organization for Economic Co‐operation and Development countries. In this paper, we examine if this deficit can be considered optimal using the Engel and Rogers's approach. In this framework, the current account of a country is determined by the expected discounted present value of its future share of world GDP relative to its current share. A country whose income is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
3
0
1
Order By: Relevance
“…In today's global economy, Turkish SMEs are not exempt from this, and they have been frequently impacted by such risks in the past two decades as well (Karadag 2016). Moreover, giving high likelihood and high impact values for financial crises and other economic risks can be explained by the fact that Turkish economy has deficit in international trade (Abbasoglu et al 2019) and highly rely on external energy sources such as oil and natural gas.…”
Section: Discussionmentioning
confidence: 99%
“…In today's global economy, Turkish SMEs are not exempt from this, and they have been frequently impacted by such risks in the past two decades as well (Karadag 2016). Moreover, giving high likelihood and high impact values for financial crises and other economic risks can be explained by the fact that Turkish economy has deficit in international trade (Abbasoglu et al 2019) and highly rely on external energy sources such as oil and natural gas.…”
Section: Discussionmentioning
confidence: 99%
“…In recent literature, many studies, for instance, references [18][19][20][21][22][23] have employed conventional unit-root tests, co-integration, VAR, VECM, and Granger causality tests to examine the relationship between CAD and FD. The present study focused on previous studies that reported the empirical findings of Southeast Asian economies only as shown in Table 2.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Turan et al (2016) note that based on the degree of cointegration between imports and exports, in the longer term the current account deficit is not sustainable. On the other hand, Abbasoğlu et al (2018), employing the approach adopted by Engel and Rogers (2006), find that the CAD is sustainable in the long-term if Turkey's growth performance relative to the rest of the world continues at a similar rate as it has in the last 15 years. Finally, external assessments, notably the IMF's External Sector Asssessment are carried out periodically, the most recent of which is part of the IMF's 2018 Article IV Consultation Staff Report.…”
Section: Overview Of Recent Literature On the Current Account In Turkeymentioning
confidence: 99%